Reading Galileo at school: some teaching ideas for Italian class - Giuseppe Zarra (Italiano a scuola)
This paper presents an example of a lesson that integrates literature and language in upper secondary school Italian classes (final three-year cycle). Starting from the reading of a passage from Dialogo sopra i due massimi sistemi del mondo by Galileo Galilei, followed by a brief linguistic commentary, the article offers didactic suggestions useful for designing Italian language teaching pathways in the final stage of secondary education.